Doctors' experience providing primary care for refugee women living with chronic pain: a qualitative study - Areni Altun; Helen Brown; Elizabeth Sturgiss; Grant Russell (BMC, 2024)
Abstract Background The experiences of GPs in Australia highlight key considerations regarding workload demands, remuneration incentives and the practical implications of working in regions with high ethnic density. This exploration helps to understand the elements that influence GPs delivery of care, particular for refugee women who exhibit disproportionately higher rates of chronic pain. This qualitative study explored the experiences of GPs providing care for refugee women living with chronic pain. Methods Semi-structured interviews were undertaken with 10 GPs (9 female and 1 male) practicing across metropolitan Melbourne, Australia. GPs were recruited via purposive sampling and a snowballing strategy. Participants work experience ranged from one to 32 years. Audio recordings of the interviews were transcribed verbatim and stored in qualitative data Nvivo 12 software for coding. Transcripts of interviews were analysed thematically using a phenomenological approach. Results Three overarching themes were identified: (1) meeting the needs of refugee women living with chronic pain; (2) the role of the GP; and (3) the challenges of the health care system. These themes reflected the complexity of consultations which arose, in part, from factors such as trust, the competencies of clinician's and the limitations posed by time, funding and interpreter use. Conclusion GPs acknowledged the uniqueness of refugee women's chronic pain needs and whilst doctors welcomed care, many were often challenged by the complex nature of consultations. Those that worked in settings that aligned with refugee women's needs highlighted the importance of cultivating culturally safe clinical environments and listening to their patients' stories. However, system level challenges such as time, funding and resource constraints created significant challenges for GPs. Exploring GPs experiences allows for a better understanding of how vectors of disadvantage intersect in health care and highlights the need to better support doctors to improve health care provision for refugee women living with chronic pain.